Breaking The Promise to Marry Unlawful Acts or Default - Ambarwati, Auliah; Rasyid, Muh. Fadli Faisal; Saharuddin, Saharuddin; Wulandari, Devi Dwi; Syahril, Muh. Akbar Fhad (JUSTISI, 2024)
This study aims to find civil law arrangements regarding the juridical analysis of breaking a promise to marry or what is commonly referred to as Broken Marriage Promises as an unlawful act. What are the legal consequences of breaking a marriage promise as unlawful? This study uses a normative legal research type with a statutory approach. The types and sources of legal materials use primary, secondary, and tertiary legal materials. Analysis of legal materials uses deductive logical reasoning, which is studied from a qualitative perspective. The results of the study show that breaking a promise to marry or commonly called promises of marriage as an unlawful act, is regulated in Article 58 of the Civil Code and several judges' decisions such as Supreme Court Decision Number 3191 K/Pdt/1984, Supreme Court Decision Number 3277 K/Pdt/2000, Decision of the Supreme Court Number 1644 K/Pdt/2020. The legal consequences of breaking a marriage promise as an unlawful act, namely if a person suffers a loss due to breaking of the marriage promise, both material and immaterial losses, then he can be sued for compensation following the loss suffered if the element of the unlawful act is fulfilled according to Article 1365 of the Civil Code.